(untitled) (Bangladesh Journal of Medical Education, 2023)
Background: Blood stream infections are an important cause of mortality & morbidity in all age group worldwide. Aim & Objective: The aim of this study was to perform bacteriological analysis and assess antibiotic sensitivity patterns of isolates from bloodstream infections in a tertiary care hospital in Dhaka city. Material & methods: The study is a retrospective observational analysis of blood culture isolates received in the Department of Microbiology, Holy Family Red Crescent Medical College & Hospital from January to December, 2021. A total sample size was 2371, out of them positive aerobic bacterial growth was observed in 85 (3.58%) isolates. Sampling technique was used to collect data from the laboratory records and written consent was taken from concerned authority collected data were compiled and analyzed with the help of SPSS version 20. All samples were collected in BacT/ ALERT 3D 60 aerobic bottles irrespective to antibiotics administration. One to five (1-5) ml blood for children and 5-10 ml blood for adult were collected respectively. Samples were incubated in the automated BacT/ ALERT 3D. Subculture was done on blood agar, chocolate agar media & MacConkey’s agar media. Identification of organisms by Gram stain & biochemical tests were done as per the standard methods. Negative signal blood culture bottles were kept in machine for up to 5 days. No mixed cultures (the association of two microorganisms) were identified. All the isolates were tested for their antimicrobial susceptibility pattern by Kirby-Bauer’s disk diffusion technique according to the Clinical and Laboratory standards institute guideline. Results: Overall, 45/874 (5.14%) positive blood cultures were isolated from adult followed by neonate 31/709(4.37%), children 6/390(1.54%) & infant 3/398(0.75%). Bacteremia was more or less equal in both sexes, female 44 (51.77%) & male 41(48.23%). Trend of pathogens recover in highest in November 13(15.29%). The most common organism isolated was Staph. aureus 26(30.58%) followed by Klebsiella species 15(17.64%), Acinetobacter species 13(15.29%), Pseudomonas species 11(12.94%), Salmonella Typhi 10(11.76%) and E. coli 10(11.76%). In Staph. aureus, linezolid and vancomycin were 100% sensitive. In Klebsiella spp. meropenem was 87% & in E. coli 80% sensitive. In Acinetobacter spp. amoxicillin/ clavanic acid 85% & colistin 70% sensitive. In Pseudomonas spp., meropenem and piperacillin tazobactum 100% sensitive followed by ciprofloxacin 82%, ceftazidime 82% & amikacin 81.8% sensitive. In Salmonella Typhi, ceftriaxone was 100% sensitive. Conclusion: Drug resistant bacteria are increasing over the years, so, antibiotic policy which formulates according to local sensitivity pattern will be implemented effectively. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 84-91